Pengembangan Modul Digital IPAS Terintegrasi Permainan Tradisional untuk Melatih Keterampilan Proses Sains Siswa Kelas IV SDN 51 Sumarambu Kecamatan Telluwanua Kota Palopo - Wahdaniyah; Arwan Wiratman; Ervi Rahmadani (Program Studi Pendidikan Sejarah - Universitas Samudra, 2025)
This study aims to develop a digital module of science and natural sciences integrated with traditional games to train students' science process skills. This study uses a mix method approach with the type of research Research and Development (R&D). The development model used is ADDIE (Analyze, Design, Development, Implementation, and Evaluation). This research was conducted at SDN 51 Sumarambu, Telluwanua District, Palopo City. The research subjects were teachers and 21 fourth-grade students with the research object of the digital module of science and natural sciences integrated with traditional games developed according to the characteristics and needs of students. From the results of the needs analysis, it shows that students prefer learning styles that involve students directly, such as learning while playing. The design of the digital module of science and natural sciences in this study is an animated video of traditional games that will be linked to learning activities regarding the types of styles. For the validity of the digital module of science and natural sciences integrated with traditional games, it was validated by 3 validators, namely the material validator with a value of 75% (valid), the language validator with a value of 87.5% (very valid), and the media/learning administration validator with a value of 78.1% (valid). The teacher's practicality test yielded a score of 85% (practical) and the student's practicality test yielded a score of 87.41% (very practical). The effectiveness test showed that the N-Gain value for each indicator ranged from 0.44 to 0.77, with a moderate to high categorization. This indicates that the digital science module integrated with traditional games effectively trains students' science process skills.